Leaders lost in transition: A case study in leadership, ritual and social capital - Nell, IA (Nederduitse Gereformeerde Teologiese Tydskrif, 2009)
We live in South Africa in a time characterised by liminality. Various shifts take place in this fluid transition phase – not just physical, often forced removals of people, but also, and particularly, shifts in power. Societies in this phase often struggle with feelings of loss and being lost. One of the areas where this feeling of loss is experienced strongly, is in the vacuum that often arises in leadership. The leaders themselves are sometimes unsure what direction to take, and there is often the danger of unethical leadership. This also occurs in faith communities. This article makes use of a case study to examine the role of leadership as part of the religious rituals in faith communities and the positive role it can play in such a liminal phase.